Higher risk for chronic graft-versus-host disease (GvHD) in HLA-G mismatched transplants following allogeneic hematopoietic stem cell transplantation: a retrospective study - Neuchel, Christine; Gowdavally, Sowmya; Tsamadou, Chrysanthi; Platzbecker, Uwe; Sala, Elisa; Wagner-Drouet, Eva; Valerius, Thomas; Kröger, Nicolaus; Wulf, Gerald; Einsele, Hermann; Thurner, Lorenz; Schaefer-Eckart, Kerstin; et al. (HLA, 2022)
Introduction Graft-versus-host disease (GvHD) is a major complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and is highly influenced by the degree of HLA matching between recipient and donor. The HLA-class Ib molecule HLA-G has been shown to promote tolerogenicity through its interaction with inhibitory receptors found on several immunocompetent cells. We hypothesized that in an allo-HSCT setting, HLA-G mismatches may negatively impact the HLA-G-mediated tolerogenicity either due to inefficient interaction with the inhibitory receptors of the transplanted immune cells or due to direct allorecognition of mismatched HLA-G on host cells by the immune cells of the donor. Methods In order to explore this hypothesis, we investigated the impact of HLA-G mismatching in 2.083 10/10 matched high resolution HLA-typed allo-HSCT transplants. Results We found that the risk of chronic GvHD was significantly higher in HLA-G-mismatched transplant cases as compared with the HLA-G-matched control group (HR: 1.46, 95%CI = 1.11-1.91, p = 0.006). Sub-analysis of the mismatch vector revealed that this effect was only detectable in the GvH (HR: 1.89, 95%CI 1.39-2.57, p < 0.001) but not the HvG direction (HR: 1.01, 95%CI = 0.63-1.63, p = 0.967). In addition, the negative impact of HLA-G mismatching on chronic GvHD was only significant in younger patients (<30y HR: 3.02, 95%CI = 1.25-7.28, p = 0.014; >29y HR: 1.28, 95%CI = 0.94-1.72, p = 0.113). Discussion Our results indicate that HLA-G mismatches may contribute to the onset of chronic GvHD, especially in younger patients and should therefore be avoided when possible.